Consumer preferences towards beef cattle in Chile: Importance of country of origin, cut, packaging, brand and price - Schnettler, Berta; Sepúlveda, Néstor; Sepúlveda, José; Orellana, Ligia; Miranda, Horacio; Lobos, Germán; Mora, Marcos (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
A study was carried out to evaluate preferences for two cuts, four countries of origin, two forms of presentation, brand and different prices of beef cattle among supermarket buyers in southern Chile, and to distinguish the existence of different market segments, through a survey of 800 people. Using a fractional factorial design for conjoint analysis, it was determined overall that the origin was more important (44.5%) than price (20.8%), form of presentation (12.2%), cut (12.0%) and brand (10.5%), with preference for Chilean and Argentinean striploin, packaged on trays, with no brand at medium price. Using a cluster analysis, three market segments were distinguished. The largest (52.3%) placed great importance on origin and preferred the highest price. The second (27.5%) also valued origin with the greatest preference for Argentinean beef, and it was the only group that preferred the ribeye as the cut. The third (20.5%) placed the greatest importance on price, and was the only group that preferred Paraguayan meat. The segments differed in the importance of eating meat for their personal well-being. The low importance of packaging and brand indicates poorly developed marketing of this product. In order to properly insert brand beef in the Chilean market, communication strategies must be implemented that identify the product with superior quality and that position the brand in the consumer’s mind.